CCN2/CTGF expression via cellular uptake of BMP‐1 is associated with reparative dentinogenesis. (30th June 2015) - Muromachi, K; Kamio, N; Matsuki‐Fukushima, M; Nishimura, H; Tani‐Ishii, N; Sugiya, H; Matsushima, K
<x xml:space="preserve">Abstract</x> Objective CCN family member 2/connective tissue growth factor (CCN2/CTGF) is known as an osteogenesis‐related molecule and is thought to be implicated in tooth growth. Bone morphogenetic protein‐1 (BMP‐1) contributes to tooth development by the degradation of dentin‐specific substrates as a metalloprotease. In this study, we demonstrated the correlations between CCN2/CTGF and BMP‐1 in human carious teeth and the subcellular dynamics of BMP‐1 in human dental pulp cells. Materials and Methods Expression of CCN2/CTGF and BMP‐1 in human carious teeth was analyzed by immunohistochemistry. BMP‐1‐induced CCN2/CTGF protein expression in primary cultures of human dental pulp cells was observed by immunoblotting. Intracellular dynamics of exogenously administered fluorescence‐labeled BMP‐1 were observed using confocal microscope. Results Immunoreactivities for CCN2/CTGF and BMP‐1 were increased in odontoblast‐like cells and reparative dentin‐subjacent dental caries. BMP‐1 induced the expression of CCN2/CTGF independently of protease activity in the cells but not that of dentin sialophosphoprotein (DSPP) or dentin matrix protein‐1 (DMP‐1). Exogenously added BMP‐1 was internalized into the cytoplasm, and the potent dynamin inhibitor dynasore clearly suppressed the BMP‐1‐induced CCN2/CTGF expression in the cells. Conclusion CCN2/CTGF and BMP‐1 coexist beneath caries lesion and CCN2/CTGF expression is regulated by dynamin‐related cellular uptake of BMP‐1, which suggests a novel property of metalloprotease in reparative dentinogenesis.